Equivalence and reduction of delay-differential systems - Boudellioua, Mohamed Salah (Zielona Góra: Uniwersytet Zielonogórski)
A new direct method is presented which reduces a given high-order representation of a control system with delays to a first-order form that is encountered in the study of neutral delay-differential systems. Using the polynomial system description (PMD) setting due to Rosenbrock, it is shown that the transformation connecting the original PMD with the first-order form is Fuhrmann's strict system equivalence. This type of system equivalence leaves the transfer function and other relevant structural properties of the original system invariant.
Keywords: polynomial matrix description; neutral delay-differential systems; strict system equivalence; determinantal ideals; Gröbner bases